Pleural involvements in pulmonary sarcoidosis: A case report and review of the literature - Ji, Xiaoqing; Lu, Jiameng; Zuo, Anli; Sun, Fei; Peng, Haiying; Lu, Degan (Frontiers in Medicine, 2022)
Sarcoidosis is a chronic, multisystemic granulomatosis of unknown origin that can aﬀect multiple organs throughout the body with variable progression and prognosis. It may be manifested as a battery of symptoms and signs. Although the lungs and mediastinal lymph nodes are almost affected in sarcoidosis, involvements of the pleurae remain uncommon. Herein, we report a case of sarcoidosis with both pleural effusions and pleural nodules as confirmed by thoracoscopic pleural biopsy.